Kebahagiaan Pemimpin Perempuan Dalam Menjalani Peran Ganda Perspektif Psikologi - Titin Nurhidayati Nurhidayati (FALASIFA : Jurnal Studi Keislaman, 2020)
Positive psychology is the flow of modern psychology that focuses its studies on the positive aspects of humans and leads people not just to live, but to live happily. One of the benefits of happiness itself is reflected through the success of women in achieving careers as leaders in the workplace and still being able to carry out their roles as wives and mothers well. The balance of their roles shows that women have the ability to be leaders in the workplace, without leaving their roles as wives and mothers in the family.